(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Azoospermia, characterized by the absence of sperm in the ejaculate, is a significant contributor to male infertility. Traditional treatment approaches often combine hormonal therapies, surgical interventions and assisted reproductive techniques, yet not all cases resolve successfully. This paper explores a treatment approach using Ayurvedic therapies. The study focuses on a 37-year-old male diagnosed with azoospermia, initially presented with the symptoms of sleeplessness, fatigue and general weakness. The patient underwent a treatment regimen including Ayurvedic formulations over a period of six months. Post-treatment evaluations revealed significant improvements: total sperm concentration increased from nil to 28 million/ml, progressive motility improved to 50%, and sperm morphology normalized with 96% of sperm showing normal forms. Subjective symptoms also showed remarkable improvement with the Insomnia Severity Index score reducing from 18 to 8, and the Fatigue Severity Scale score reducing from 45 to 25. These findings suggest that integrating Ayurvedic medicine with conventional treatments can effectively enhance fertility outcomes and overall quality of life in patients with azoospermia. The study advocates for further research through larger clinical trials to validate and potentially standardize this integrative treatment approach.